THE ADVANTAGES OF BILINGUAL EDUCATION BY SPECIAL REFERENCE TO LINGUISTIC, CULTURAL AND PEDAGOGICAL RATIONALES IN TEFL AT ENGLISH EDUCATION DEPARTMENT OF FKIP UNISMUH MAKASSAR - Hamid, Radiah (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2017)
The using of bilingual in education means using two languages for instructional purposes. Specially in teaching learning in English Education Department of FKIP Unismuh Makassar, most of the teachers use English and Indonesian for instructional purposes. Based on this phenomenon, this article aims to show the advantages of the using this bilingual education by concerning linguistic, cultural, and pedagogical rationales. The article will discuss about propositions according to the three rationales by concerning the empirical facts in teaching learning process done by teachers at English Education Department of FKIP Unismuh Makassar. The facts of teaching learning process have been observed from classrooms of the teachers who teach English speciality subjects, such as ‘Structure’, ‘Teaching English as Foreign Language’, and ‘Phonetic/Phonology’.  This article  shows how the two languages using, for instance viewed by linguistic rationale, can influence each other through borrowing grammatical and phonological change and a bilingual education helps to control such influences. In referring to cultural rationale, a bilingual education ensures that a minority ethnic group safeguards its original native culture while participating in modernizing and innovating tendencies. The last, the proposition concerning the pedagogical rationale  shows that using first language is a good basis for learning a foreign language.